Analisis Penyerapan Tenaga Kerja Sektor Industri Manufaktur Besar dan Sedang di Indonesia - Suci Febriani; Alpon Satrianto; Selli Nelonda (Universitas Negeri Padang, 2022)
This study aims to determine and analyze how influence of wages, output, capital and tax on employment in the large and middle manufacturing sector in Indonesia. This research type is descriptive and inductive research. This research type is descriptive and inductive research. This study uses panel data regression analysis using the Fixed Effect Model (FEM) method. The data used is secondary panel regression data with a combination of 24 sub-sectors of large and medium manufacturing industries in Indonesia from 2010- 2019 obtained from related institutions and then analyzed using a panel regression model by testing classical assumptions. The results of the study show that simultaneously, wages and output have a significant effect on employment in the large and medium manufacturing sector in Indonesia. Meanwhile, capital and taxes have no significant effect on employment. Furthermore, partially (1) wages have a positive and significant effect on employment, (2) output has a positive and significant effect on employment, (3) capital has a positive and insignificant effect on employment, (4) taxes have a positive effect and are not significant to employment.